Electrical properties of Er2O3-Doped potassium sodium niobate based silicate glass - Yongsiri P. (2017)
© Copyright 2017 American Scientific Publishers All rights reserved. In this study, the electrical properties of Er 2 O 3 doped potassium sodium niobate (KNN) based silicate (SiO 2 ) glass has been investigated. This glass-ceramic system was successfully prepared via the incorporation method. The selected compositions used in this experiment were 70-80 mol% of KNN and 20-30 mol% of SiO 2 , doped with 0.5 mol% Er 2 O 3 . From the study, the resulted KNN glass-ceramics greatly improved the dielectric constant at room temperature (ϵr = 250 at 10 kHz) above those found using a conventional glass-ceramic method, with a very low tan below 0.1. It was found that temperature and frequency have significantly influenced on dielectric properties of the KNN glass-ceramics. The study of polarization mechanism via dielectric measurement found that this glass system had space-charge polarization and relaxation at low frequency. The results also showed that the electrical properties of the material arised mainly due to the bulk effects. P -E hysteresis loops of all glasses and glass-ceramic samples exhibited rugby ball-like loops which confirmed the high leakage current.